Phenomenological Model for Defect Interactions in Irradiated Functional Materials - Steven J. Brewer; Cory D. Cress; Samuel C. Williams; Hanhan Zhou; Manuel Rivas; Ryan Q. Rudy; Ronald G. Polcawich; Evan R. Glaser; Jacob L. Jones; Nazanin Bassiri-Gharb (Scientific Reports, 2017)
Abstract The ability to tailor the performance of functional materials, such as semiconductors, via careful manipulation of defects has led to extraordinary advances in microelectronics. Functional metal oxides are no exception – protonic-defect-conducting oxides find use in solid oxide fuel cells (SOFCs) and oxygen-deficient high-temperature superconductors are poised for power transmission and magnetic imaging applications. Similarly, the advantageous functional responses in ferroelectric materials that make them attractive for use in microelectromechanical systems (MEMS), logic elements, and environmental energy harvesting, are derived from interactions of defects with other defects (such as domain walls) and with the lattice. Chemical doping has traditionally been employed to study the effects of defects in functional materials, but complications arising from compositional heterogeneity often make interpretation of results difficult. Alternatively, irradiation is a versatile means of evaluating defect interactions while avoiding the complexities of doping. Here, a generalized phenomenological model is developed to quantify defect interactions and compare material performance in functional oxides as a function of radiation dose. The model is demonstrated with historical data from literature on ferroelectrics, and expanded to functional materials for SOFCs, mixed ionic-electronic conductors (MIECs), He-ion implantation, and superconductors. Experimental data is used to study microstructural effects on defect interactions in ferroelectrics.